Social Studies Teachers' Attitudes Concerning Convtroversial Public Issues Instruction and State Mandated Tests - (:unkn) unknown (My University, 2012)
This transcendental phenomenological qualitative study examines attitudes toward Controversial Public Issue instruction by teachers who used mandated standards and state tests. After the interviews of 11 social studies teachers (high school, middle school and junior high) five distinct themes emerged in the study. Overall, participants execute Controversial Public Issues instruction regardless of the void in state standards. Each participant expressed her/his own attitudes concerning Controversial Public Issue instruction; however, there were also definite commonalities. Ten participants planned Controversial Public Issues in their classroom regardless of obstacles stated in previous research.
Keywords: United States--Politics and government--Study and teaching--Public opinion; Civics--Study and teaching--Public opinion; Social studies teachers--United States--Attitudes; Public opinion--United States